Pretreated Sugarcane Bagasse Result in more Efficient Degradation by Streptomyces sp S2 - Stanislaus Aditya Agung; Rismawati .; Dede Heri Yuli Yanto; Anja Meryandini; Titi Candra Sunarti (Microbiology Indonesia, 2022)
Streptomyces genera plays an important role in lignocellulose degradation. Many research found that Streptomyces have cellulolytic and ligninolytic enzymes that are sufficient to degrade lignocellulosic materials. However, a minimum lignocellulosic material condition that can efficiently be degraded by sp. has Streptomyces not been fully understood. In this research, three pretreatment conditions (physical, alkaline-hydrothermal, and hydrogen-peroxide chemical treatments) of sugarcane bagasse were used as lignocellulosic material to be further degraded by Streptomyces sp. S2. Lignocellulose component measurement concluded that raw (physically treated only) bagasse was not efficiently degraded by Streptomyces sp S2. Hydrogen-peroxide was effective in reducing both syringic and guaiacyl lignin. Meanwhile, alkaline-hydrothermal pretreatment was very effective in lowering syringic lignin. This study suggests that hydrogen-peroxide pretreatment can be used in any type of lignocellulosic material, which can be further degraded by Streptomyces sp. S2. On the other hand, alkaline hydrothermal pretreatment is best suited to degrade lignocellulosic material with a high percentage of syringic lignin. Key words: Alkaline-hydrothermal treatment, Hydrogen peroxide treatment, lignocellulose, Streptomyces sp. S2, sugarcane bagasse